2013
DOI: 10.1002/cctc.201200906
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of N‐Substituted Aspartic Acids Using an Engineered Variant of Methylaspartate Ammonia Lyase

Abstract: Scheme 1. Biocatalytic synthesis of a few N-substituted l-aspartic acids.[a] Dr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Enzymatic products were purified by two steps of ion-exchange chromatography. [20] The purified products were lyophilized and their identity was determined by using 1 H NMR, 13 C NMR and HRMS. The enantiomeric excess and absolute configuration of the product was determined by HPLC analysis on a chiral stationary phase.…”
Section: Communications Ascwiley-vchdementioning
confidence: 99%
See 2 more Smart Citations
“…Enzymatic products were purified by two steps of ion-exchange chromatography. [20] The purified products were lyophilized and their identity was determined by using 1 H NMR, 13 C NMR and HRMS. The enantiomeric excess and absolute configuration of the product was determined by HPLC analysis on a chiral stationary phase.…”
Section: Communications Ascwiley-vchdementioning
confidence: 99%
“…[19] Using MAL-Q73A, a large variety of Nsubstituted L-aspartic acids were synthesized with high enantioselectivity (> 99% e.e.). [20] Structural analysis of MAL-Q73A showed that this mutant enzyme has an enlarged amine binding pocket, without changes in the orientation of active site residues, thus rationalizing its ability to convert the new amine substrates. [19] Recently, we reported another CÀ N lyase, ethylenediamine-N,N'-disuccinic acid (EDDS) lyase from Chelativorans sp.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has previously reported that an engineered variant of 3-methylaspartate ammonia lyase (MAL-Q73A) accepts various amines, including butylamine (2 c, Table 1), for enantioselective hydroamination of fumarate (1). [21,22] Structurally, the amines 2 b and 2 a have, respectively, one and two extra methyl group(s) at C3 compared with 2 c. This difference prompted us to start our investigations by testing the branched amines 2 a and 2 b as unnatural substrates in the MAL-Q73A-catalyzed hydroamination of 1. Although 2 b was accepted by MAL-Q73A for slow hydroamination of 1 (see Figure S1 in the Supporting Information), yielding optically pure l-3 b (ee > 99 %), 2 a was unfortunately not accepted as a substrate by MAL-Q73A.…”
Section: Resultsmentioning
confidence: 99%
“…MALs belong to the enolase superfamily and they catalyze a broader range of reactions than other ammonia lyases [1] They are potentially versatile and a promising target to design new variants with different substrate specificity or improved activity and stability. For example, the MAL variant isolated from Citrobacter amalonaticus (CaMAL) has been engineered for enantionselective synthesis of N-substituted aspartic acids, which are essential building blocks for pharmaceutical, artificial sweeteners, synthetic enzymes and peptidomimetics [10,11].…”
Section: Introductionmentioning
confidence: 99%